Sonographic Findings of Nasopharyngeal Carcinoma and Its Involvement in the Parapharyngeal Space. (1st June 2013) - Pan, Dai; Zhu, Shang-Yong; Xu, Yuan-Bing; Wu, Ya-Fei; Lun, Hai-Mei; Wei, Yu-Ya
Abstract : Objectives: The purpose of this study was to determine the sonographic performance in pathologically proven cases of nasopharyngeal carcinoma and its involvement in the parapharyngeal space. Methods: The study included 58 patients being treated for suspected nasopharyngeal carcinoma detected by routine nasopharyngoscopy who underwent pathologic biopsy. Sonography was performed immediately thereafter with a convex array transducer in both the B‐mode and color mode. Forty‐five of the 58 patients (90 parapharyngeal spaces) in whom nasopharyngeal carcinoma was proved by both sonography and pathologic biopsy underwent preradiotherapy magnetic resonance imaging (MRI). The sonographic findings were compared to the pathologic findings. The sonographic findings of parapharyngeal space involvement were correlated with the MRI findings. Results: The normal anatomy of the nasopharynx and parapharyngeal space, nasopharyngeal carcinoma, and its relationship with the parapharyngeal space were well shown on sonography. The sensitivity of sonography for detection of nasopharyngeal carcinoma was 97.8%, and the specificity was 41.7%. The sonographic findings of parapharyngeal space involvement had a high degree of agreement with MRI (κ = 0.757; P < .001). Conclusions: These promising initial data indicate that sonography may be a useful tool for diagnosing nasopharyngeal carcinoma and defining the relationship between the tumor and the parapharyngeal space.